A comprehensive review on emerging trends in industrial wastewater research - Malik, Sumira; Kishore, Shristi; Prasad, Shilpa; Shah, Maulin P. (Journal of basic microbiology, 2022)
Rapid industrialization is one of the intricate factors that is linked to the depletion of water resources and increased generation of wastewater. Due to various obstructions and impediments, such as ineffective treatment solutions, exorbitant prices, lack of basic amenities, insufficient financial assistance, and technical expertise, sustainable treatment of industrial effluents has become an onerous process in most parts of the world. The majority of current treatment solutions are conventional and outdated, and thus fall short to remove all the contaminants efficiently from the industrial wastewater. Moreover, poorly treated or untreated industrial effluents are indiscriminately dumped into water bodies such as lakes, ponds, and rivers, causing substantial health hazards to humans and animals and serious threats to the aquatic ecosystem. Thus, there is a need for highly efficient, cost‐effective, and sustainable technologies for the treatment of industrial wastewater. Employment of microbial technologies such as microbial fuel cells and microalgal technologies, treatment of wastewater can be coupled with the production of bioelectricity and valuable biomass, respectively. Moreover, with nanofiltration and biochar technologies, the efficiency of the overall treatment procedure can be increased to a greater extent. The present review aims to highlight opportunities and challenges associated with some of the emerging trends in industrial wastewater research.